Model Pemasaran Syariah Pengembangan Usaha Coffee Shop di Masa Pandemi Covid-19 - Sarah Nurjanah; Yayat Rahmat (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Indonesia experienced a period of the Covid-19 pandemic that attacked the Indonesian people so that the PSBB system was implemented, this had an impact on the economic sector, including entrepreneurs engaged in the coffee shop, although there were many impacts caused by the corona virus outbreak, Bambamkuy Coffee shop experienced significant growth. The purpose of this study is to find out the concept and marketing strategy according to Islam, to know the Islamic marketing model in the development of the bambam.kuy caffee shop business in the midst of the covid-1 pandemic. The research method used is qualitative, the data sources used are primary data in the form of interviews and secondary data in the form of books, literature, journals. Collecting data through observation, interviews, documentation. Data analysis techniques in the form of data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the sharia concept applied to the BambamKuy coffee shop is in accordance with the sharia marketing concept. Applying the concept of sharia marketing mix (marketing mix shari'a) and four characteristics of shari'a marketing, namely, Theitis or Divinity (Rabbaniyah), Ethical (Akhlaqiyyah), Realistic (Al-Waqi'iyyah), and Humanistic (Al-Insaniyyah). Coffee shop BambamKuy has also imitated the marketing practices of the Prophet Muhammad SAW, namely market segmentation and targeting, positioning, sharia marketing tactics, sharia marketing value. Abstrak. Indonesia mengalami masa pandemi Covid-19 yang menyerang masyarakat Indoneisa sehingga diberlakukannya sistem PSBB, hal ini berdampak pada sektor perekonomian termasuk para pengusaha yang bergerak di bidang coffee shop, meski banyak dampak yang ditimbulkan akibat wabah virus corona ini Coffee shop Bambamkuy mengalami pertumbuhan yang signifikan. Tujuan penelitian ini yaitu untuk mengetahui konsep dan strategi pemasaran menurut Islam, mengetahui model pemasaran Syariah pada pengembangan usaha caffee shop bambam.kuy ditengah pandemic covid-1. Metode penelitian yang digunakan ialah kualitataif, sumber data yang digunakan yaitu data primer berupa wawancara dan data sekunder berupa buku, literatur, jurnal. Pengumpulan data melalui observasi, wawancara, dokumentasi. Teknik analisis data berupa pengumpulan data, reduksi data, penyajian data dan penarikan kesimpulan. Hasil dari penelitian ini menunjukan bahwa konsep syariah yang diterapkan pada coffee shop BambamKuy telah sesuai dengan konsep pemasaran syariah. Menerapkan konsep bauran pemsaran syariah (marketing mix syari’a) dan empat karakteristik marketing syari’a yaitu, Teitis atau Ketuhanan (Rabbaniyah), Etis (Akhlaqiyyah), Realistis (Al-Waqi’iyyah), dan Humanitis (Al-Insaniyyah). Coffee shop BambamKuy juga Telah mencontoh praktik pemasaran Nabi Muhammad SAW yaitu segmentasi pasar dan targeting, positioning, sharia marketing tactics, sharia marketing value.